HUBUNGAN PARITAS TERHADAP BERAT LAHIR DI RSUD PANGERAN JAYA SUMITRA - Ika Friscila; Hafsah Us; Aida Fitriani; Erlina Erlina (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Health development is one of the National Development efforts. The high and low infant mortality rate (IMR) is mostly influenced by low birth weight. Various efforts to improve the quality of human resources since in the womb have been carried out, one of which is by screening high-risk pregnant women. The purpose of this study was to analyze the relationship between parity and birth weight in the Balleradja room at RSUD Pangeran Jaya Sumitra. This study uses a quantitative research design. The study population was all postpartum mothers who were hospitalized in the Balleradja room at RSUD Pangeran Jaya Sumitra, totaling 31 people. The sample is 31 people (using total sampling technique). The research was conducted in the Balleradja room at RSUD Pangeran Jaya Sumitra. Conducted in February 2022. Data collection using a questionnaire. Data were analyzed by univariate and bivariate. Univariate analysis to present the data results into a frequency distribution table. While the bivariate analysis used the Spearman Rank correlation test with a 95% confidence level. The analytical tool in this study is SPSS 20.0. The results showed that there was no relationship between parity and birth weight of infants in Prince Jaya Sumitra Hospital (p value = 0.778 or p value > 0.05).